The Influence of Loan to Deposit Ratio (LDR) and Operating Costs on Operating Income (BOPO) on Return on Assets (ROA): Study On One of The Banks in Bandung - Chinthia Cahya Mega; Bulan Tati Fitria; Roro Endah Kumalasari; Indah Damayanti; Adam Ramdani (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study examines the influence of LDR and BOPO on ROA at a bank in Bandung. Return on Assets (ROA) highlights the Company's ability to produce revenue from its operations by efficiently using its assets. Factors affecting Return on Assets (ROA) encompass the Loan to Deposit Ratio (LDR) and the Operating Expenses to Operating Income Ratio (BOPO), all of which impact ROA. The study's population consisted of four years of financial records from a bank in Bandung, encompassing all four quarters. The sample was selected using the time series approach, consisting of 16 financial reports from 2018 to 2021. The applied data testing method was multiple linear regression, utilizing a significance level of 5% alpha. The findings indicated that LDR did not exert a significant influence on ROA. Despite LDR exhibiting a positive coefficient, the significance value is above the conventional threshold, suggesting that the impact of LDR on ROA is minimal and statistically insignificant. Conversely, BOPO substantially impacts ROA, with a negative coefficient and a minimal significance value. The rise in BOPO, signifying diminished operational efficiency, adversely affects ROA, suggesting that elevated operating costs diminish the bank's profitability. Subsequent research indicated that the regression model accounts for most of the variation in ROA, demonstrating a robust association between LDR and BOPO with ROA. It is advised that the Company's management concentrate on optimizing operating cost management to enhance ROA. Implementable strategies encompass conducting frequent audits to identify and mitigate waste and enhancing the efficiency of operational procedures. Despite LDR not demonstrating a significant impact, it is crucial to monitor this ratio to ensure the bank's liquidity and financial stability. This study also advocates for additional research to investigate other variables that may influence ROA, along with a comprehensive examination of operational elements to enhance profitability.